Preparation method of fracturing sand with good suspension capacity for fracturing fluid
By hydrophobic and hydrophilic modification of quartz sand, the effective density is reduced, and the problem of poor suspension capacity of existing fracturing sand is solved, good suspension and transport performance in fracturing fluid is achieved, and oil and gas is improved Yield.
Patent Information
- Application Number
- CN202411574265.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
Existing fracturing sand such as natural quartz sand has high relative density and poor suspension capacity, making it difficult to effectively suspend in fracturing fluid, and cannot meet the requirements of deep fracturing support.
After pretreatment of the quartz sand, a hydrophobic modifier and a hydrophilic modifier are added for modification. The hydrophobic modifier consists of surfactants, hydrophobic polymers, ethylenediamine, silica sol and siloxanes. The hydrophilic modifier consists of hydrophilic polymers, silica sol and 3-mercaptopropyltrimethoxysilane. The surface of the quartz sand is formed by stirring and drying and hydrophilic groups are introduced to reduce its effective density.
The modified quartz sand has good suspension capability and conveying performance, and can remain suspended at high flow rates, smoothly enter the cracks and form effective support, improving the conveying efficiency of fracturing fluid, thereby increasing the oil and gas production.
Smart Images

Figure CN119432359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing fracturing sand for fracturing fluid with good suspension ability. Background Art
[0002] As an important means of oil and gas production, fracturing technology is widely used in the exploitation of unconventional oil and gas resources. This technology injects high-pressure liquid (fracturing fluid) into the formation to create cracks in the formation, thereby increasing the permeability and production capacity of oil and gas in the rock. In the fracturing process, fracturing sand, as a key proppant, is a key material in oil and gas production, especially in hydraulic fracturing technology. Its main function is to reduce the resistance to oil and gas flow by maintaining the open state of the cracks, increase the flow rate of oil and gas, and thus increase oil and gas production.
[0003] However, with the increase in mining depth and the complexity of geological conditions, the performance requirements for fracturing sand are getting higher and higher. Existing fracturing sand (such as natural quartz sand) has a high relative density and poor suspension ability in fracturing fluid, which makes it unable to effectively suspend in the fracturing fluid (suspended in the liquid and flow with the liquid), making it difficult to follow the fracturing fluid to reach deeper locations and unable to meet the requirements of fracturing support. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing fracturing sand for fracturing fluid with good suspension ability, which can effectively reduce the relative density of natural quartz sand so that it can be effectively suspended in the fracturing fluid.
[0005] Technical solution: The method for preparing fracturing sand for fracturing fluid of the present invention comprises the following steps:
[0006] (1) Pre-treating quartz sand;
[0007] (2) adding the pretreated quartz sand to the hydrophobic modifier, stirring thoroughly, filtering and drying; wherein the hydrophobic modifier is composed of the following components by weight: 0.1-0.2 parts of a surfactant, 1-2 parts of a hydrophobic polymer, 3-4 parts of ethylenediamine (ethylenediamine adjusts the pH value to alkaline so that the particle size of the silica sol is not too large. If the particle size is large, the hydrophobic shell is easy to fall off from the quartz sand, which increases the surface friction when it contacts with other substances, resulting in falling off, thereby greatly reducing the hydrophobic / hydrophilic properties of the fracturing sand), 1-3 parts of silica sol, 0.5-0.6 parts of siloxane and 100 parts of water;
[0008] (3) adding the hydrophobically modified quartz sand to the hydrophilic modifier, stirring thoroughly, and then adding hydrogen peroxide thereto (hydrogen peroxide has strong oxidizing properties, making it easy for the hydrophilic modifier to be grafted onto the surface of the hydrophobic layer). After sufficient reaction, filtering and drying are performed to obtain the final product; wherein the hydrophilic modifier is composed of the following components in parts by weight: 1 to 3 parts of a hydrophilic polymer, 1 to 3 parts of silica sol, 2 to 4 parts of 3-mercaptopropyltrimethoxysilane, and 100 parts of water.
[0009] Wherein, in step (2), the hydrophobic polymer is at least one of polydimethylsiloxane, polytetrafluoroethylene, polyvinylidene fluoride or ethylene-ethylene-chlorotrifluoroethylene copolymer.
[0010] Wherein, in step (2), the surfactant is one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine or polyoxyethylene alkanolamide.
[0011] Wherein, in step (2), the siloxane is one of trimethylethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane or phenyltriethoxysilane.
[0012] Wherein, in step (2), the hydrophobic treatment is performed so that the hydrophobic modifier completely covers the quartz sand, and the immersion and stirring are continued for more than 1 hour so that the quartz sand and the hydrophobic modifier are fully in contact, so that the hydrophobic groups are directly grafted onto the surface of the quartz sand.
[0013] Wherein, in step (3), the hydrophilic polymer is at least one of polyvinyl alcohol, polyethylene glycol or polyacrylic acid.
[0014] Wherein, in step (3), the hydrophilic treatment is performed, the hydrophilic modifier completely covers the hydrophobically modified quartz sand, and the stirring is continued for more than 1 hour during immersion and stirring, so that the hydrophobized quartz sand is fully in contact with the hydrophilic modifier, the hydrophilic group is grafted on the surface of the hydrophobic layer, the hydrophobic layer is wrapped on the surface of the quartz sand, the hydrophilic group is grafted on the hydrophobic layer, and the density of the hydrophilic group grafting is thinner than that of the hydrophobic layer.
[0015] Wherein, in step (3), the amount of hydrogen peroxide added is 0.1 to 0.25% of the amount of water added in the hydrophilic modifier.
[0016] Wherein, in step (2) and step (3), the silica sol is spherical, with a particle size of 4 to 7 nm and a solid content of 15%.
[0017] Wherein, in step (2), the reaction temperature of the hydrophobic modifier and the hydrophilic modifier during the preparation process is 50-60° C. At this temperature, the activity of the hydrophobic polymer is relatively high and it is easy to graft.
[0018] After the quartz sand is hydrophobized, the present invention introduces some hydrophilic groups, so that the overall modified quartz sand becomes a non-uniform body, and the effective density is reduced (the density of quartz sand is 2.65g / cm3, and after hydrophobization, it is equivalent to wrapping a layer of shell on the surface of quartz sand, and the shell can only swell but not melt, so that the suspension ability of the proppant is stronger; the density of the hydrophobic shell is smaller than that of quartz sand, and the density after swelling is even smaller, thereby achieving a reduction in effective density). At the same time, because it has both hydrophobic characteristics and hydrophilic functions, it can avoid being completely repelled by the fracturing fluid, so that the modified quartz sand can be effectively suspended in the fracturing fluid.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: Compared with ordinary fracturing sand (unmodified quartz sand), the self-suspending fracturing support quartz sand prepared by the present invention exhibits excellent suspension and transportation performance in fracturing operations (can be suspended in water, flow with the water body, and will not sink to the bottom), can maintain a good suspension state at high flow rates, smoothly enter the cracks and form effective support; its good dispersibility in the fracturing fluid can greatly improve the transportation efficiency of the fracturing fluid with fracturing sand, thereby improving its operating efficiency during the application process, and then increasing the production of oil and gas, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a comparison diagram of the water contact angle of quartz sand before and after modification in Example 1, wherein a is before modification and b is after modification;
[0021] Figure 2 This is a physical comparison diagram of quartz sand in water before and after modification in Example 1, where: Figure 2 The left side corresponds to the modified one. Figure 2 The right side corresponds to before modification;
[0022] Figure 3 This is a schematic diagram of the water contact angle of quartz sand in Example 1;
[0023] Figure 4 This is a schematic diagram of the water contact angle of quartz sand in Example 2;
[0024] Figure 5 Schematic diagram of the water contact angle of quartz sand in Example 3. DETAILED DESCRIPTION
[0025] Example 1
[0026] The method for preparing fracturing sand for fracturing fluid of the present invention specifically comprises the following steps:
[0027] (1) Pre-treating the quartz sand; after ultrasonic cleaning, the quartz sand is heated at 120° C. for 5 hours until the quality is stable, and the pre-treatment is used to remove the moisture and adsorbed impurities contained in the quartz sand; the mesh size of the selected quartz sand is 40 to 70 meshes;
[0028] (2) preparing a hydrophobic modifier: adding 0.1 parts by mass of alkylphenol polyoxyethylene ether, 1 part by mass of polydimethylsiloxane, 3 parts by mass of ethylenediamine having a mass fraction of 25 to 28%, and 1 part by mass of silica sol to 100 parts by mass of water under a water bath heating condition maintained at 50° C., mixing the mixture evenly, and then adding 0.5 parts by mass of trimethylethoxysilane thereto, stirring the mixture sufficiently, to obtain a solution A;
[0029] (3) adding the quartz sand pretreated in step (1) to solution A, stirring continuously for 1 hour to allow the quartz sand to fully contact with solution A, then filtering the quartz sand and drying it at 120° C. to obtain hydrophobicized quartz sand; when adding the quartz sand, solution A should completely cover the quartz sand;
[0030] (4) preparing a hydrophilic modifier: adding 1 part by mass of polyvinyl alcohol and 1 part by mass of silica sol to 100 parts by mass of water under heating conditions at 50° C., mixing them evenly, then adding 2 parts by mass of 3-mercaptopropyltrimethoxysilane, stirring them thoroughly, to obtain a solution B;
[0031] (5) Add the product of step (3) (hydrophobically modified quartz sand) to solution B, stir for 1 hour, and then add hydrogen peroxide solution (the mass fraction of hydrogen peroxide solution is 30%), the amount of hydrogen peroxide added is 0.1wt% of the amount of water added in the hydrophilic modifier; after sufficient stirring, filter and dry at 100°C to obtain the final product. The water contact angle of the quartz sand obtained in Example 1 is as follows: Figure 3 As shown, the water contact angle is 130°.
[0032] Example 2
[0033] The method for preparing fracturing sand for fracturing fluid of the present invention specifically comprises the following steps:
[0034] (1) Pre-treating the quartz sand; after ultrasonic cleaning, the quartz sand is heated at 120° C. for 6 hours until the quality is stable, and the pre-treatment is used to remove the moisture and adsorbed impurities contained in the quartz sand; the mesh size of the selected quartz sand is 70 to 140 meshes;
[0035] (2) Preparation of a hydrophobic modifier: adding 0.2 parts by mass of fatty acid polyoxyethylene ester, 2 parts by mass of polytetrafluoroethylene, 4 parts by mass of ethylenediamine having a mass fraction of 25-28%, and 3 parts by mass of silica sol to 100 parts by mass of water under a water bath heating condition maintained at 60° C., mixing the mixture evenly, and then adding 0.6 parts by mass of ethyltriethoxysilane thereto, stirring the mixture sufficiently, to obtain a solution A;
[0036] (3) adding the quartz sand pretreated in step (1) to solution A, stirring continuously for 1 hour to allow the quartz sand to fully contact with solution A, then filtering the quartz sand and drying it at 120° C. to obtain hydrophobicized quartz sand; when adding the quartz sand, solution A should completely cover the quartz sand;
[0037] (4) Preparation of a hydrophilic modifier: Add 3 parts by mass of polyethylene glycol and 3 parts by mass of silica sol to 100 parts by mass of water under heating conditions at 60° C., mix well, then add 4 parts by mass of 3-mercaptopropyltrimethoxysilane, stir well, and obtain a solution B;
[0038] (5) Add the product of step (3) (hydrophobically modified quartz sand) to solution B, stir for 1 hour, and then add hydrogen peroxide solution (the mass fraction of hydrogen peroxide solution is 30%), the amount of hydrogen peroxide added is 0.1wt% of the amount of water added in the hydrophilic modifier; after sufficient stirring, filter and dry at 100°C to obtain the final product. The water contact angle of the quartz sand obtained in Example 2 is as follows: Figure 4 As shown, the water contact angle is 134°.
[0039] Example 3
[0040] The method for preparing fracturing sand for fracturing fluid of the present invention specifically comprises the following steps:
[0041] (1) Pre-treating the quartz sand; after ultrasonic cleaning, the quartz sand is heated at 120° C. for 6 hours until the quality is stable, and the pre-treatment is used to remove the moisture and adsorbed impurities contained in the quartz sand; the mesh size of the selected quartz sand is 70 to 140 meshes;
[0042] (2) Preparation of a hydrophobic modifier: adding 0.15 parts by mass of polyoxyethylene alkylamine, 1.5 parts by mass of polyvinylidene fluoride, 3.5 parts by mass of ethylenediamine having a mass fraction of 25 to 28%, and 2 parts by mass of silica sol to 100 parts by mass of water under a water bath heating condition maintained at 55° C., mixing the mixture evenly, and then adding 0.55 parts by mass of propyltrimethoxysilane thereto, stirring the mixture sufficiently, to obtain a solution A;
[0043] (3) adding the quartz sand pretreated in step (1) to solution A, stirring continuously for 1 hour to allow the quartz sand to fully contact with solution A, then filtering the quartz sand and drying it at 120° C. to obtain hydrophobicized quartz sand; when adding the quartz sand, solution A should completely cover the quartz sand;
[0044] (4) Preparation of a hydrophilic modifier: Add 2 parts by mass of polyacrylic acid and 2 parts by mass of silica sol to 100 parts by mass of water under heating conditions maintained at 55° C., mix well, then add 3 parts by mass of 3-mercaptopropyltrimethoxysilane, and stir thoroughly to obtain a solution B;
[0045] (5) Add the product of step (3) (hydrophobically modified quartz sand) to solution B, stir for 2 hours, and then add hydrogen peroxide solution (the mass fraction of hydrogen peroxide solution is 30%), the amount of hydrogen peroxide added is 0.2wt% of the amount of water added in the hydrophilic modifier; after sufficient stirring, filter and dry at 100°C to obtain the final product. The water contact angle of the quartz sand obtained in Example 3 is as follows: Figure 5 As shown, the water contact angle is 144°.
[0046] Example 4
[0047] The method for preparing fracturing sand for fracturing fluid of the present invention specifically comprises the following steps:
[0048] (1) Pre-treating the quartz sand; after ultrasonic cleaning, the quartz sand is heated at 120° C. for 6 hours until the quality is stable, and the pre-treatment is used to remove the moisture and adsorbed impurities contained in the quartz sand; the mesh size of the selected quartz sand is 70 to 140 meshes;
[0049] (2) Preparation of a hydrophobic modifier: 0.15 parts by mass of polyoxyethylene alkanolamide, 1.5 parts by mass of ethylene-chlorotrifluoroethylene copolymer, 3.5 parts by mass of ethylenediamine having a mass fraction of 25-28%, and 2 parts by mass of silica sol were added to 100 parts by mass of water under a water bath heating condition maintained at 55° C. After mixing evenly, 0.55 parts by mass of phenyltrimethoxysilane was added thereto, and after sufficient stirring, a solution A was obtained;
[0050] (3) adding the quartz sand pretreated in step (1) to solution A, stirring continuously for 1 hour to allow the quartz sand to fully contact with solution A, then filtering the quartz sand and drying it at 120° C. to obtain hydrophobicized quartz sand; when adding the quartz sand, solution A should completely cover the quartz sand;
[0051] (4) Preparation of a hydrophilic modifier: Add 2 parts by mass of polyacrylic acid and 2 parts by mass of silica sol to 100 parts by mass of water under heating conditions maintained at 55° C., mix well, then add 3 parts by mass of 3-mercaptopropyltrimethoxysilane, and stir thoroughly to obtain a solution B;
[0052] (5) Add the product of step (3) (hydrophobically modified quartz sand) to solution B, stir for 2 hours, and then add hydrogen peroxide solution (the mass fraction of hydrogen peroxide solution is 30%), wherein the amount of hydrogen peroxide added is 0.2 wt % of the amount of water added in the hydrophilic modifier; after sufficient stirring, filter and dry at 120° C. to obtain the final product.
[0053] Example 5
[0054] The method for preparing fracturing sand for fracturing fluid of the present invention specifically comprises the following steps:
[0055] (1) Pre-treating the quartz sand; after ultrasonic cleaning, the quartz sand is heated at 120° C. for 6 hours until the quality is stable, and the pre-treatment is used to remove the moisture and adsorbed impurities contained in the quartz sand; the mesh size of the selected quartz sand is 70 to 140 meshes;
[0056] (2) Preparation of a hydrophobic modifier: 0.13 parts by mass of polyoxyethylene alkanolamide, 1.3 parts by mass of ethylene-chlorotrifluoroethylene copolymer, 3.2 parts by mass of ethylenediamine having a mass fraction of 25-28%, and 2 parts by mass of silica sol were added to 100 parts by mass of water under a water bath heating condition maintained at 57° C. After mixing evenly, 0.58 parts by mass of phenyltrimethoxysilane was added thereto, and after sufficient stirring, a solution A was obtained;
[0057] (3) adding the quartz sand pretreated in step (1) to solution A, stirring continuously for 1 hour to allow the quartz sand to fully contact with solution A, then filtering the quartz sand and drying it at 120° C. to obtain hydrophobicized quartz sand; when adding the quartz sand, solution A should completely cover the quartz sand;
[0058] (4) Preparation of a hydrophilic modifier: 1.5 parts by mass of polyacrylic acid and 2.2 parts by mass of silica sol were added to 100 parts by mass of water under heating conditions maintained at 57° C., and after uniform mixing, 2.6 parts by mass of 3-mercaptopropyltrimethoxysilane was added thereto, and after sufficient stirring, a solution B was obtained;
[0059] (5) Add the product of step (3) (hydrophobically modified quartz sand) to solution B, stir for 2.5 hours, and then add hydrogen peroxide solution (the mass fraction of hydrogen peroxide solution is 30%), wherein the amount of hydrogen peroxide added is 0.25wt% of the amount of water added in the hydrophilic modifier; after sufficient stirring, filter and dry at 110° C. to obtain the final product.
[0060] Comparative Example 1
[0061] Compared with Example 3, the preparation method of Comparative Example 1 is basically the same as that of Example 3, with the only difference being that only the quartz sand is hydrophobically modified, and there is no hydrophilic modification step of steps (4) to (5).
[0062] The quartz sand before modification, the quartz sand prepared in Example 3 and the quartz sand prepared in Comparative Example 1 were subjected to application experiments simulating the suspension in the fracturing fluid, specifically: Suspension test experiment: 40g of the quartz sand before modification, the quartz sand prepared in Example 3 and the quartz sand prepared in Comparative Example 1 were mixed with clean water to prepare a sand-carrying liquid with a sand-water ratio of 15wt%, and a mechanical stirrer was used, and the mechanical stirring speed was set to 200RPM. The uniformly stirred sand-carrying liquid was poured into a 10mL measuring cylinder, and the time required for the uppermost quartz sand to settle to the 1-grid mark was recorded. The test results are shown in Table 1:
[0063] Table 1
[0064] Sample name Suspension time (min) Quartz sand before modification 5 Example 3 40 Comparative Example 1 20
[0065] The experimental results show that the quartz sand with hydrophobic modification and hydrophilic modification (Example 3) has better suspension than the quartz sand with only hydrophobic modification (Comparative Example 1), and the quartz sand with only hydrophobic modification (Comparative Example 1) has better suspension than the quartz sand before modification. Therefore, the suspension effect of quartz sand with hydrophobic modification and hydrophilic modification is the best.
Claims
1. A method for preparing fracturing sand for fracturing fluid with good suspension ability, characterized in that: The steps include: (1) Pre-treating quartz sand; (2) adding the pretreated quartz sand to a hydrophobic modifier, stirring thoroughly, filtering and drying; wherein the hydrophobic modifier is composed of the following components in parts by weight: 0.1 to 0.2 parts of a surfactant, 1 to 2 parts of a hydrophobic polymer, 3 to 4 parts of ethylenediamine, 1 to 3 parts of silica sol, 0.5 to 0.6 parts of siloxane and 100 parts of water; (3) adding the hydrophobically modified quartz sand to the hydrophilic modifier, stirring sufficiently, and then adding hydrogen peroxide thereto, filtering and drying after sufficient reaction to obtain a final product; wherein the hydrophilic modifier is composed of the following components in parts by weight: 1 to 3 parts of a hydrophilic polymer, 1 to 3 parts of silica sol, 2 to 4 parts of 3-mercaptopropyltrimethoxysilane, and 100 parts of water.
2. The preparation method according to claim 1, characterized in that: In step (2), the hydrophobic polymer is at least one of polydimethylsiloxane, polytetrafluoroethylene, polyvinylidene fluoride or ethylene-chlorotrifluoroethylene copolymer.
3. The preparation method according to claim 1, characterized in that: In step (2), the surfactant is one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine or polyoxyethylene alkanolamide.
4. The preparation method according to claim 1, characterized in that: In step (2), the siloxane is one of trimethylethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane or phenyltriethoxysilane.
5. The preparation method according to claim 1, characterized in that: In step (2), the hydrophobic modifier completely immerses the quartz sand, and the immersion and stirring are continued for more than 1 hour.
6. The preparation method according to claim 1, characterized in that: In step (3), the hydrophilic polymer is at least one of polyvinyl alcohol, polyethylene glycol or polyacrylic acid.
7. The preparation method according to claim 1, characterized in that: In step (3), the hydrophilic modifier completely immerses the hydrophobically modified quartz sand, and the immersion and stirring are continued for more than 1 hour.
8. The preparation method according to claim 1, characterized in that: In step (3), the amount of hydrogen peroxide added is 0.1 to 0.25% of the amount of water added in the hydrophilic modifier.
9. The preparation method according to claim 1, characterized in that: In step (2) and step (3), the reaction temperature of the hydrophobic modifier and the hydrophilic modifier during the preparation process is 50-60°C.
10. Fracturing sand prepared by the preparation method according to any one of claims 1 to 9.